Acceptance of COVID-19 Vaccine in Undergraduate Students at Peshawar, Pakistan - Aziza Alam; Ibrahim Akhtar; Hamza Khan; Ayma Asad; Aleesha Gulalay Amjad; Ismail Alam Khan (ziauddin University, 2024)
Background: Although vaccines are an effective tool for tackling COVID-19, hesitancy exists in Pakistan. The objectives were to find the acceptance of COVID-19 vaccines and the causes of vaccine hesitancy among non-medical undergraduate students of Peshawar University. Methods: This cross-sectional study, was conducted from March 2021 to July 2022, using a validated closed-ended structured questionnaire. A pilot study was done on 32 students (10% of the sample) at Agriculture University with Cronbach's alpha 0.7. By non-probability convenient sampling, 315 undergraduate students from the Psychology Department, Economics, and Institute of Management Studies of Peshawar University were included. The data was analyzed using SPSS v.23. Categorical variables were presented in the form of frequency and percentages. The chi-square test was applied with a p<0.05 as a significant. Results: Among 315 participants, 45.7% (144) males and 54.3% (171) females of which 264(83.8%) were vaccinated. 45(14.3%) of the participants showed acceptance of COVID-19 vaccine. Acceptance of the COVID-19 vaccine didn't show any statistical significance when compared with different age groups and gender with p=0.54 and p=0.86 respectively. Misconceptions, myths, and ignorance were the main factors for vaccine hesitancy. Studies showed that gender and COVID-19 vaccines were being promoted for the commercial gains of pharmaceutical companies with a p<0.001. Moreover, different departments considered fertility as a cause of hesitancy (p<0.001). Conclusion: It is concluded that misconceptions, fear of needles, and commercial gains of pharmaceutical companies, were the reasons for vaccine hesitancy which can be addressed by providing mass health education and targeting the vulnerable population. Keywords: COVID-19, Vaccines, Vaccination Hesitancy.